Proverka odnoi gipotezy i komentarii k nei v aspekte teorii i praktiki sporta - Matveev, L. P.; Gasanova, Z. A. (Teorija i Praktika fiziceskoj Kul'tury, 2001)
Biorhythmology still had no time to illuminate all problems. In its present state it is easy to notice the return proportionality between the degree of explore of various biorhythms and their extent in a time: the rather short biorhythms are explored in details, but biorhythms shown in limits of larger time scales, are displayed with smaller details and with smaller severity of the analysis in the research publications. It is especially distinctive for the available characteristics of long-term biorhythms. It is not enough of the generalizing publications devoted to them. The longer the phase of biorhythms, the more time and resources it is required to spend by the researcher even externally to look after them and to penetrate into the essence of principles determining the changes of biorhythms. Macrobiorhythms gradually attract the increasing research attention.